Comparative study of web annotation systems used by learners to enhance educational practices: features and services. (2016) - Kalboussi, Anis; Mazhoud, Omar; Kacem, Ahmed Hadj
In educational context, and with the emergence of web information technology, the need for annotation tools becomes more and more claimed and felt, because annotation practice is common and omnipresent. While reading, learner usually uses comments, highlights and circles sections to tag digital documents. Therefore, many systems have been developed in the learning environment to help learner to annotate different electronic-consulted resources. This great variety of annotation systems, which is usually considered as an enrichment of the educational community, reveals a lack of a clear strategy of how to compare developed annotation systems of the literature according to their features and services to facilitate learner the choice of an annotation system that allows to enhance learning. As a result, few works have tried to present comparative studies of these tools. The aim of this article is to provide a study of some annotation tools used by learners in educational practices. Therefore, we present a comparison of services provided by 40 annotation systems developed by industry and academia during the last decade. As a second contribution, we classify these annotation tools based on transversal features. Finally, the study further reveals gaps in systems and opportunities for further research.